Impact of socio-demographic variables on antenatal services in eastern Uttar Pradesh, India. Issue 4 (1st July 2021) - Bala, Renu; Singh, Ajay; Singh, Vertika; Verma, Priyanka; Budhwar, Snehil; Shukla, Om Prakash; Singh, Gyan Prakash; Singh, Kiran
Abstract: We investigated the impact of socio-demographic variables on antenatal care (ANC) utilization and the low birth weight of a child. Data were collected from 300 pregnant females. Only 22.5% of females received full antenatal care (≥4 visits). Our results showed that female's age at marriage and education plays a significant role in improving ANC. We observed an overall decrease in the utilization of services provided during each antenatal visit. ANC visits from the first trimester decrease the risk of having a baby with low birth weight. Awareness programs and educating families about pregnancy care are recommended to improve ANC utilization.